The impact of broken homes on the learning motivation of students: Case Study in elementary school in North Lombok, Indonesia - Wulandari, Wulandari; Musafir, Musafir; Mulyono, Ana (Panicgogy International Journal, 2023)
This research aims to describe the impact of broken home families on the learning motivation of grade 4 students at SDN 3 Rempek darusallam for the 2023/2024 academic year.This research is a descriptive type of qualitative research.Data collection techniques use observation,interviews,and documentation.The data obtained was analyzed descriptively by reducing the data,presenting the data and drawing conclusions.test the validity of the data or check the data using source triangulation.The results of this research show that broken home families tend to have less motivation to learn,3 students tend to be less,so that children are less motivated in learning.Children become lazy about studying,lazy about going to school,and enthusiastic about learning,and indifferent to the learning process.